Antibacterial activity of water extracts and essential oils of various aromatic plants against Paenibacillus larvae, the causative agent of American Foulbrood - González, María J. (2010)
Vegetal water extracts, namely the water remaining after hydro-distillation and decoctions, and essential oils of 10 plant species were tested as inhibitors for the growth of Paenibacillus larvae, the causative agent of American Foulbrood. Achyrocline satureioides, Chenopodium ambrosioide, Eucalyptus cinerea, Gnaphalium gaudichaudianum, Lippia turbinata, Marrubium vulgare, Minthostachys verticillata, Origanum vulgare, Tagetes minuta and Thymus vulgaris were included in the study. The water remaining after hydro-distillation showed the highest antibacterial activities, the growth of almost all the P. larvae strains tested was inhibited by these extracts. Regarding the plants tested, E. cinerea and M. verticillata were the plant species with the highest biological activity with 100% efficacy (all its extracts inhibited the growth of all P. larvae strains). Essential oils were less active for the inhibition of P. larvae growth.